Metallic mineral deposits of Peru - Tumialán De la Cruz, Pedro Hugo (1998)
Morphologically in Peru eleven zones are observed, with a peculiar metallic mineralization in each one of them. Geotectonically there was a hercinic orogenesis in the coastal chain in the Eastern Cordillera with an Eohercinic tectonism in the Upper Devonian, neohercinic tectonism in the Middle Permian; Andean orogenesis in the Western, Central and Sub-Andean Cordillera from the Upper Cretaceous to the Upper Tertiary. The metallic deposits have a distribution in stripes parallel to the Andes Mountains known as metallogenetic provinces; from West to East there is: iron, copper, within it gold in a certain sector, silver and polymetallic, polymetallic, gold and polymetallic, gold panning, with a peculiar geology in each of them. These metallogenetic provinces have been mineralized at different times known as metallogenetic times, they were made with the Paleozoic, Upper Cretaceous-Lower Tertiary, Upper Tertiary, and the Quaternary. Everything expressed was carried out by the effect of the convergence plate tectonism known as the Nazca Plate and the American Plate, which gave rise to the formation of the Andes Mountains, its magmatism and its mineralization.